CLINICO-BIOCHEMICAL PROFILE OF DENGUE IN A TERTIARY CARE HOSPITAL - Dr. Anup Kumar Budhia; Dr Kalikinkar Chand; Dr Bhabani Sankar Samantaray; Dr Bapuji Nayak; Dr Bijayalaxmi Parija (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Dengue fever, a mosquito-borne viral illness, is a serious public health concern in India, presenting as recurrent epidemics and leading to severe morbidity and mortality. Dengue infection is a risk for about 25% of the world's population, primarily those living in tropical and subtropical regions.Aim: The current study set out to evaluate epidemiology, clinico-biochemical spectrum, the radiological findings and prognosis of dengue fever in order to identify better indicators of the illness in patients. Material & methods: This was a Prospective review conducted in the period from August 2023 to December 2023 in adults suffering from Dengue fever. Dengue was confirmed by testing NS1 AG, IgG, and IgM in the patients. After admission various detailed clinical evaluation and investigations were carried out to find out the required data and information. Result: A total of 60 patients with dengue were diagnosed, with the majority being men. The symptoms included high-grade fever(100%), severe myalgia and headache(90%), arthralgia(90%), vomiting and loose motion(50%), shortness of breath(17%), abdominal swelling(10%), haemorrhagic manifestations(10%), gum bleeding(4%), upper GI bleeding(2%), and haematuria(2%). Anomalies in the blood count (CBC) output were found, including leukopenia(69%), thrombocytopenia(77%), lymphocytosis(38%), eosinopenia(57%), neutrophils(20%), and PCV(33%). Liver function tests (LFT) and renal function tests (RFT) revealed abnormalities linked to dengue, such as elevated AST levels(93%), raised ALT levels(70%), total bilirubin(10%), decreased protein levels(67%), and decreased serum calcium(34%) and phosphate(9%). Anomalies were also observed in the electrocardiogram, X-ray, and ultrasonography reports, with 25.5% showing sinus bradycardia, (18.33%) showing pleural effusion, and (11.7%) showing mild to moderate ascites. Conclusion: When a patient was diagnosed with dengue, symptoms such as a high grade fever, thrombocytopenia, elevated AST and ALT levels, sinus bradycardia on the ECG, effusion on X-ray reports, and ascites on ultrasonography were all found to be associated with dengue fever.